Morphometric and Meristic Characters of a Small Indigenous Freshwater Balitorid, Triplophysa marmorata (Cypriniformes, Nemacheilidae), from Manasbal Lake, Kashmir, India - Mushtaq, S. T.; Mushtaq, S. A.; Shah, T. H.; Bhat, F. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
The current study investigates the morphometric and meristic characteristics of a small indigenous freshwater balitorid, Triplophysa marmorata, thriving in Manasbal Lake, Kashmir, India. The research involved the collection of 360 samples of Triplophysa marmorata from Manasbal Lake. A detailed investigation was carried out on 18 morphometric and 6 meristic characters of Triplophysa marmorata specimen whose length ranged from 28.66 to 164.1 cm. The analysis revealed that the morphometric measurements were dependent on body size and there was a gradual increase in body length. Regression analysis was performed between the independent variables TL and the dependent variables viz. SL, FL, PrAL, PrVL, PrDL, BD, HL, CFL, PFL and PVL as well as between the dependent variables HL and the dependent variables ED, SnL, PrOL and PoL. The results indicated a positive relation between various morphometric characters and both TL and HL, displaying correlations that ranged from medium to high strength. On the other hand the fish showed constant meristic characters where there was no change in meristic counts with the increase of body length. The fin formula is derived as D 6–9; P 8–10; V 6–7; A 4–6; C 13–18. The findings demonstrated characteristic morphometric traits exclusive to Triplophysa marmorata in Manasbal Lake establishing crucial data for future investigations into the biological dynamics and conservation objectives pertaining to the fish.